The Veterinary profession in Greece: Review of the present and prospects for the future. A. The Hellenic Veterinary Medical Society: Organisation, Role, and Goals - ΧΑΤΖΗΟΛΟΣ, Β. (Journal of the Hellenic Veterinary Medical Society, 2019)
The revolutionary progress in science and technology during the last few decades has provided new avenues for the improvement of the veterinary profession, but, simultaneously, it brought with it new responsibilities for improving the quality of our society. There is an urgency to redefine the goals of the veterinary profession. The increase of the role of the Hellenic Veterinary Medical Society and the unification under its auspices of the various veterinary groups are strongly recommended. Included among the duties of the Society should be (1) the enlightenment of the public with regard to the responsibilities of the veterinarian; (2) the establishment of various committees to provide studies on, make recommendations for, and, if necessary exert pressure for achieving the eradication of zoonoses, for the improvement of public health and the environment, for the development of farm animals — a problem which will remain unsolved without the repeal of the unscientific and discriminatory law which excludes veterinarians, even specialists in animal science, from positions related to animal husbandry —, for the broadening of veterinary education, and, in general, for the solution of animal problems pertaining to public health and welfare and to the nation's economy; and (3) the organization of annual national veterinary meetings and, from time to time, of meetings with veterinary organizations of neighboring countries. Finally, the financial sources for implementing the above activities are also discussed.